2017
DOI: 10.1007/s13197-017-2522-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of clinical genotype Vibrio vulnificus in clam samples in Mangalore, Southwest coast of India

Abstract: Vibrio vulnificus is an opportunistic human pathogen causing gastroenteritis, wound infection and primary septicemia. V. vulnificus population has been divided into subpopulations based on their phenotype and genotype characteristics. In this study, 38.5% (10/26) of clam (Meretrix meretrix) samples obtained from Mangalore markets were seen to harbor V. vulnificus. Biochemical characterization of V. vulnificus isolates showed the strains to belong to Biotype 1 phenotype. Genotyping of strains using the 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Based on polymorphism in CPS operon and the vcg gene, it was confirmed that seafood isolates in the present study are of the clinical type. Environmental isolates possessing the C genotype have been previously reported from this region [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on polymorphism in CPS operon and the vcg gene, it was confirmed that seafood isolates in the present study are of the clinical type. Environmental isolates possessing the C genotype have been previously reported from this region [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, V. vulnificus causes large epidemics of mortality in many other species of fish and the infected fish shows severe hemorrhagic body lesions (Li et al, 2006). Prevalence studies of V vulnificus in India demonstrated its presence in the waters and wild caught fish and shellfish (Thampuran and Surendran, 1998;Parvathi et al, 2004;Sangeetha et al, 2017). However, pathological significance of V. vulnificus in fish cultured in Indian cage waters is not known till date.…”
Section: Discussionmentioning
confidence: 99%
“…He reported that up to 50% and 11% of the shellfish and crabs, respectively, were culture positive for Vibrio species during the months of summer. In India, studies have indicated presence of Vibrio vulnificus in the oysters and clams ranging from 16.6% to 56.6% 9–11. Though India has a long coastline and many people depend on fishing for their livelihood, not many cases of Vibrio vulnific us infection have been reported in the country probably due to lack of awareness among the clinicians and laboratory personnel, or proper cooking of seafood before consumption.…”
Section: Discussionmentioning
confidence: 99%